Effects of Solvents on the Antimicrobial Activities of Crude Extracts Produced from Conocarpus species Leaves - Dhurgham Alhasan (مجلة علوم ذي قار, 2025)
This study aimed to determine the most effective solvent for extracting antimicrobial compounds from powdered leaves of Conocarpus species. The powdered leaves were extracted separately using petroleum ether, aqueous methanol (80%), and chloroform. The antimicrobial activity of each crude extract was tested against several pathogenic microorganisms at various concentrations. The aqueous methanol extract demonstrated the strongest antimicrobial activity against Candida albicans, Staphylococcus aureus, Streptococcus mutans, and Escherichia coli compared to the petroleum ether and chloroform extracts. The minimum inhibitory concentrations (MICs) varied for each solvent; for instance, E. coli was inhibited by all extracts at 5 µg/ml, whereas at 1000 µg/ml, none of the extracts exhibited antimicrobial activity against S. aureus. Additionally, S. mutans and C. albicans were inhibited by the aqueous methanol extract at 1000 µg/ml, while the same concentration of petroleum ether and chloroform extracts did not affect the growth of S. mutans. Furthermore, concentrations ranging from 100 to 1000 µg/ml of all extracts inhibited Klebsiella species. Phytochemical tests indicated that the petroleum ether extract contains alkaloids and terpenoids, while the chloroform extract contains terpenoids only. In contrast, the aqueous methanol extract contained terpenoids, glycosides, phenolic compounds, flavonoids, tannins, and saponins. Gas chromatography-mass spectrometry (GC-MS) analysis identified various compounds in all extracts, highlighting similarities and differences in retention times (RTs) and peak areas.